2021
DOI: 10.3390/ph14050473
|View full text |Cite
|
Sign up to set email alerts
|

DNA Aptamers against Vaccinia-Related Kinase (VRK) 1 Block Proliferation in MCF7 Breast Cancer Cells

Abstract: Vaccinia-related kinase (VRK) 1 is a serin/threonine kinase that plays an important role in DNA damage response (DDR), phosphorylating some proteins involved in this process such as 53BP1, NBS1 or H2AX, and in the cell cycle progression. In addition, VRK1 is overexpressed in many cancer types and its correlation with poor prognosis has been determined, showing VRK1 as a new therapeutic target in oncology. Using in vitro selection, high-affinity DNA aptamers to VRK1 were selected from a library of ssDNA. Select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Previously, it was shown that VRK1 expression could promote cell proliferation in myeloma by regulating cell cycle-related proteins [18]. Te current study found that the inhibition of LUSC cell proliferation was due to depletion of VRK1, which induces the cell cycle arrest in the G0/G1 phase, which is also consistent with Carrion-Marchante et al [19]. VRK1 promotes cell proliferation and migration in gastric cancer cells [14], esophageal squamous cell carcinoma [20], bladder cancer [21], and we derived the same results in LUSC.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, it was shown that VRK1 expression could promote cell proliferation in myeloma by regulating cell cycle-related proteins [18]. Te current study found that the inhibition of LUSC cell proliferation was due to depletion of VRK1, which induces the cell cycle arrest in the G0/G1 phase, which is also consistent with Carrion-Marchante et al [19]. VRK1 promotes cell proliferation and migration in gastric cancer cells [14], esophageal squamous cell carcinoma [20], bladder cancer [21], and we derived the same results in LUSC.…”
Section: Discussionsupporting
confidence: 91%
“…In cancer cells, VRK activates TNFα/NF‐κB signaling by phosphorylating IKKβ, and regulates cell cycle and DNA damage response (Figure 8 ). 224 , 225 It was demonstrated that VRK2 is a specific therapeutic target, and its inhibitor combined with PD‐1 blockade may be effective in improving immunotherapy in patients with cancers. 226 …”
Section: Kinase Groupsmentioning
confidence: 99%
“…In cancer cells, VRK activates TNFα/NF-κB signaling by phosphorylating IKKβ, and regulates cell cycle and DNA damage response (Figure 8). 224,225 It was demonstrated that VRK2 is a specific therapeutic target, and its inhibitor combined with PD-1 blockade may be effective in improving immunotherapy in patients with cancers. 226 2.8.4 DNA-dependent protein kinase DNA-dependent protein kinase (DNA-PK) is a type of kinase that phosphorylates nuclear DNA helicase II/RNA helicase A and hnRNP proteins in an RNA-dependent manner.…”
Section: Ck1-vrk Familymentioning
confidence: 99%
“…Molecules directed against BAF1 or VRK1 are actively searched as anticancer agents. For examples, DNA aptamers targeting specifically VRK1 were found to efficiently block proliferation of MCF7 breast cancer cells ( Carrión-Marchante et al., 2021 ). Various small molecules selectively targeting VRK1 have also been identified and designed ( Couñago et al., 2017 ; Serafim et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%